Obesity surgery in patients with end-stage organ failure: is it worth it? - Billeter, Adrian; Zumkeller, Michael; Brock, Judith; Herth, Felix; Zech, Ulrike; Zeier, Martin; Rupp, Christian; Wagenlechner, Petra; Mehrabi, Arianeb; Müller, Beat P. (Surgery for obesity and related diseases, 2022)
BACKGROUND: Little is known about the long-term outcomes of patients with end-stage organ failure (ESOF) undergoing obesity surgery. - OBJECTIVE: To investigate the perioperative and mid-term outcomes of patients with ESOF undergoing obesity surgery. SETTING: University hospital, Germany. METHODS: A total of 1 094 patients undergoing obesity surgery from 2006 to 2019 were screened. Inclusion criteria were ejection fraction <30%, continuous oxygen/noninvasive ventilation therapy, liver cirrhosis, or kidney failure stage 4/5. ESOF patients were compared with matched standard (MS) patients without advanced organ failure and matched for age, gender, body mass index (BMI), operation type, diabetes, arterial hypertension, and sleep apnea. RESULTS: Twenty-seven ESOF patients (56% female, age 50.3 ± 8.6, BMI 53.8 ± 8.7 kg/m2) were identified. Eighty-five percent had a sleeve gastrectomy. Mid-term total weight loss was 26.6% ± 9.0% in the ESOF patients versus 17.8% ± 11.1% in MS patients (P = .181). Long-term improvement of type 2 diabetes was comparable (ESOF: HbA1C 8.79 ± 2.06% to 6.25±1.17%, P = .047; MS: HbA1C 7.94 ± 2.02% to 7.2 ± 1.28%; P = .343). Depression scores (Patient Health Questionnaire 9) among ESOF patients improved from 13.0 ± 6.3 to 6.1 ± 5.8 (P = .004) but without significant change in MS patients (9.4 ± 7.3 to 4.3 ± 5.7; P = .082). Lung function improved in all patients although only 15% were off oxygen therapy. Treatment goals were achieved in >50% of the other groups. Major complications occurred in 11% (ESOF) versus 4% (MS) of patients (P = .299) with one death in the ESOF group (4%). CONCLUSION: Both groups had similar outcomes regarding weight loss and co-morbidity improvement. Depression only improved significantly in the ESOF group. Patients with ESOF should not be precluded from obesity surgery. Further investigation is needed to define optimized selection criteria.